2016
DOI: 10.1016/j.ajhg.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MAFB Function in Humans and Mice Causes Duane Syndrome, Aberrant Extraocular Muscle Innervation, and Inner-Ear Defects

Abstract: Duane retraction syndrome (DRS) is a congenital eye-movement disorder defined by limited outward gaze and retraction of the eye on attempted inward gaze. Here, we report on three heterozygous loss-of-function MAFB mutations causing DRS and a dominant-negative MAFB mutation causing DRS and deafness. Using genotype-phenotype correlations in humans and Mafb-knockout mice, we propose a threshold model for variable loss of MAFB function. Postmortem studies of DRS have reported abducens nerve hypoplasia and aberrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 35 publications
0
78
0
1
Order By: Relevance
“…The primary DRS phenotype, however, was recently shown to arise from developmental absence of the abducens nerve and the subsequent ectopic innervation of its lateral rectus muscle target by the oculomotor nerve (24). These data suggest that CHN1 mutations are more likely to cause primary defects in abducens rather than oculomotor nerve development.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…The primary DRS phenotype, however, was recently shown to arise from developmental absence of the abducens nerve and the subsequent ectopic innervation of its lateral rectus muscle target by the oculomotor nerve (24). These data suggest that CHN1 mutations are more likely to cause primary defects in abducens rather than oculomotor nerve development.…”
Section: Introductionmentioning
confidence: 52%
“…We report that CHN1 mutations identified in human patients, when modeled in the mouse, cause primary abducens nerve stalling within the mesenchyme, preventing the abducens nerve from contacting the lateral rectus muscle. Within the orbit, the oculomotor nerve sends stereotypical aberrant branches to misinnervate the lateral rectus, which has recently been shown to also occur secondarily to the absence of abducens motor neurons (24). Together, these studies strongly indicate that DRS results from a primary developmental insult to the abducens nucleus or nerve that prevents its innervation of the lateral rectus.…”
Section: Chn1mentioning
confidence: 59%
See 2 more Smart Citations
“…Mafb was first described as a gene related to musculoaponeurotic fibrosarcoma, and now is known to be the responsible gene for the Kreisler mutant ( kr/kr ) and Duane syndrome, characterized by inner ear defects and segmentation abnormalities in rhombomeres during early embryogenesis [49, 50]. Yu et al indicated that Mafb works downstream of Gata3 and contributed to synaptogenesis between IHCs and type I PANs [51].…”
Section: Resultsmentioning
confidence: 99%